2017
DOI: 10.1590/2359-3997000000258
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes-associated genetic variants of FTO, LEPR, PPARg, and TCF7L2 in gestational diabetes in a Brazilian population

Abstract: Objective: Gestational diabetes mellitus (GDM) is a metabolic disorder that shares pathophysiologic features with type 2 diabetes mellitus. The aim of this study was to investigate the association of the polymorphisms fat mass and obesity-associated (FTO) rs1421085, leptin receptor (LEPR) rs1137100, rs1137101, peroxisome proliferator-activated receptor gamma (PPARg) rs1801282, and transcription factor 7-like 2 (TCF7L2) rs7901695 with GDM. Subjects and methods: 252 unrelated Euro-Brazilian pregnant women were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 68 publications
1
25
1
1
Order By: Relevance
“…Some of TCF7L2 polymorphisms have been found to be associated with GDM in other populations (10)(11)(12)(13). The authors have found no relation between these polymorphisms with GDM in this Brazilian studied population (9).…”
contrasting
confidence: 50%
See 1 more Smart Citation
“…Some of TCF7L2 polymorphisms have been found to be associated with GDM in other populations (10)(11)(12)(13). The authors have found no relation between these polymorphisms with GDM in this Brazilian studied population (9).…”
contrasting
confidence: 50%
“…evaluated the polymorphisms of several genetic variants that are associated with T2D. The authors studied gene polymorphisms T2D-related such as fat mass and obesity-associated (FTO), leptin receptor (LEPR), peroxisome proliferatoractivated receptor gamma (PPARγ), and transcription factor 7-like 2 (TCF7L2) (9). These polymorphisms are related to food intake, energy balance, appetite regulation, gene expression transcription, glucose and lipids metabolism, inflammation and proliferation of pancreatic beta cells.…”
mentioning
confidence: 99%
“…Genetic studies of the transcription factor 7 like 2 ( TCF7L2 ) gene, which is arguably one of the most important T2D susceptibility genes [ 36 ], produced varying results in GDM [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. TCF7L2 encodes a transcription factor, which is involved in Wnt signaling, an important pathway that regulates glucose homeostasis.…”
Section: Single-nucleotide Polymorphismsmentioning
confidence: 99%
“…One of the five studies investigating rs7901695 found an association between GDM and the T allele in American Caucasians [ 46 ], while one study found that the C allele, rather than the T allele, was associated with GDM in a large Swedish population [ 43 ]. The three studies that did not show an association had relatively small sample sizes [ 40 , 41 , 45 ]. Of the five studies investigating rs12255372, two showed an association between the T allele and GDM, one was conducted in a large Swedish population and the other in a small Mexican population [ 42 , 43 ].…”
Section: Single-nucleotide Polymorphismsmentioning
confidence: 99%
See 1 more Smart Citation